Poverty traps and Index-Based risk transfer products - Barnett, B.J.; Barrett, Christopher B.; Skees, J.R. (Elsevier, 2008)
A growing literature suggests that in low-income countries, households with few assets can be trapped in chronic poverty. This article reviews relevant threads of the poverty traps literature to motivate a description of the opportunities presented by innovative index-based risk transfer products. These products can be used to address some insurance and credit market failures that contribute to the persistence of poverty among households in low-income countries. Applications are considered at the micro, meso, and macro levels.